Neuropathic pain in peroneal nerve entrapment at the fibular head - İlker Öztürk; Halit Fidanci; Zülfikar Arlier (Arquivos de Neuro-Psiquiatria)
Background Peroneal neuropathy at the fibular head (PNFH) is a mononeuropathy that typically presents with drop foot and sensory abnormalities over the skin area innervated by the peroneal nerve. Objective The aim of the present study was to evaluate neuropathic pain in patients with PNFH. Methods Patients with clinical and electrodiagnostic features consistent with PNFH associated with weight loss, leg postures, or prolonged sleep were included in the present retrospective cohort study. Nerve conduction studies were performed in the bilateral lower extremities of all patients. The Leeds assessment of neuropathic symptoms and signs scale (LANSS) was applied to all patients. Results Thirty-two PNFH patients (78% males) were included in the study. The LANSS score in the majority of patients was lower than 12. There was 1 patient with a LANSS score of 12. The electrodiagnostic features of 16 patients were compatible with axonal degeneration. The mean LANSS scores of PNFH patients with and without axonal degeneration were 4.3 ± 3.7 and 5.2 ± 2.9, respectively (p = 0.255). Conclusion The present study showed that neuropathic pain is a rare symptom in patients with PNFH associated with weight loss, leg postures, or prolonged sleep.